Not Even Past: Information Aging and Temporal Privacy in Online Social Networks. (4th March 2017) - Ayalon, Oshrat; Toch, Eran
Abstract : Online social networks (OSNs) make information accessible for unlimited periods and provide easy access to past information by arranging information in time lines or by providing sophisticated search mechanisms. Despite increased concerns over the privacy threat that is posed by digital memory, there is little knowledge about retrospective privacy: the extent to which the age of the exposed information affects sharing preferences. In this article, we investigate how information aging impacts users' sharing preferences on Facebook. Our findings are based on a between-subjects experiment ( n = 272), in which we measured the impact of time since first publishing an OSN post on its sharing preferences. Our results quantify how willingness to share is lower for older Facebook posts and show that older posts have lower relevancy to the user's social network and are less representative of the user's identity. We show that changes in the user's social circles, the occurrence of significant life changes and a user's young age are correlated with a further decrease in the willingness to keep sharing past information. We discuss our findings by juxtaposing digital memory theories and privacy theories and suggest a vision for mechanisms that can help users manage longitudinal privacy.